Mulheres, intelectuais e professoras : a história das mulheres pelo olhar feminino de historiadoras da região colonial italiana do Rio Grande do Sul - Dala Zen, Daiane (My University, 2024)
This thesis focuses on the study of the life trajectories, teaching experiences, and scientific production of Caxias do Sul's female teachers and historians: Cleci Eulalia de Favaro, Heloisa Delia Eberle Bergamaschi, Loraine Slomp Giron, and Maria Abel Machado. Throughout their academic and professional lives, they conducted research on the History of Women in the Italian Colonial Region (RCI). The main objective of this text was to investigate their life paths and professional development that led these teachers to become researchers in the History of omen while contributing to the education of teachers in the Metropolitan Region of Caxias do Sul. The defended thesis marks the life paths and scientific production of four Caxias do Sul historians and professors who played a prominent role in constructing the History of Women in the Italian Colonial Region. They also distinguished themselves in the production and mediation of regional history knowledge. As intellectuals and professors, they held leadership positions in the Department of History and Geography at the University of Caxias do Sul from 1961 to 2010. Their research culminated in publications that brought the discussion of women's work to the forefront, especially in the 1990s. This initiative can be understood as a form of feminism, even if not explicitly identified by that term. The theoretical and methodological approach of this study is rooted in the perspective of Cultural History in dialogue with the History of Education by Bastos (2016) and the History of Women by authors Perrot (1997, 2005, 2008), Soihet (2007), Rago (1995, 2019), Colling (2015), Pedro (1997, 2005, 2012), Louro (1997, 2000), Pinto (2003, 2010), Méndez (2017), and Prinsky (2012). For these analyses, concepts such as Gender by Scott (1989, 1994, 2012); Intellectual Mediators by Gomes (2018) and Sebrian (2017); Biography and Autobiography by Bueno (2021); and Representation by Chartier (2002) and Ego-document by Cunha (2019) were mobilized. Regarding methodology, Content Analysis by Bardin (1977) was employed for constructing biographies and life trajectories, along with the assumptions of Oral History. The historians reated representations of immigrant women and their descendants that deviate from the stereotypical pattern shaped bypatriarchy. This study delves into the history of women who conducted research on the history of other women. The History of Women, as portrayed by these respective historians, represents determined and dynamic women who, in their roles as aughters, sisters, wives, mothers, daughters-in law, and sisters-in-law, had to manage work in small properties, service provision, and also as labor in the nascent industry of Caxias do Sul. The research conducted by these four historians on women revealed the protagonism of women in regional scientific production on the History of Women, from a perspective of diverse feminisms. [resumo fornecido pelo autor]
Esta tese tem como tema o estudo dos itinerários de vida, de docência e de produção científica das professoras e historiadoras caxienses Cleci Eulalia de Favaro, Heloisa Delia Eberle Bergamaschi, Loraine Slomp Giron e Maria Abel Machado, que, ao longo de suas vidas acadêmicas e profissionais, produziram pesquisas sobre a História das Mulheres da Região Colonial Italiana (RCI). O objetivo principal deste texto foi investigar seus itinerários de vida e percurso de formação profissional que tornaram as professoras pesquisadoras sobre a História das Mulheres, ao mesmo tempo que contribuíram para a formação de professoras e professores da Região Metropolitana de Caxias do Sul. A tese que defendo marca o itinerário de vida e a produção científica de quatro historiadoras e professoras caxienses que protagonizam a construção da História das Mulheres na Região Colonial Italiana e também se destacaram na produção e mediação de conhecimento da história regional, como intelectuais e como professoras ocuparam cargos de direção e chefia do Departamento de História e Geografia, da Universidade de Caxias do Sul, entre os anos de 1961 a 2010. Suas pesquisas culminaram em publicações que trouxeram para o debate, nos anos 1990, principalmente, o trabalho feminino. Essa iniciativa pode ser compreendida como uma forma de feminismo, mesmo que não haja identificação direta com o termo. A abordagem teórica e metodológica deste estudo está inserida na perspectiva da História Cultural em diálogo com a História da Educação de Bastos (2016) e História das Mulheres das autoras Perrot (1997, 2005, 2008), Soihet (2007), Rago (1995, 2019) Colling (2015), Pedro (1997, 2005, 2012), Louro (1997, 2000), Pinto (2003, 2010), Méndez (2017) e Prinsky (2012). Para essas análises, foram mobilizados os conceitos de Gênero de Scott (1989, 1994, 2012); Intelectuais Mediadores/as de Gomes (2018) e Sebrian (2017); Biografia e Autobiografia de Bueno (2021); e Representação de Chartier (2002) e Egodocumento de Cunha (2019). Quanto a metodologia, foi realizada a Análise de Conteúdo de Bardin (1977), para a construção das biografias e itinerários de vida e docência, bem como os pressupostos da História Oral. As historiadoras constituíram representações dessas mulheres imigrantes e de suas descendentes que fogem do padrão estereotipado moldado pelo patriarcado. Este estudo versa sobre uma história de mulheres que produziram pesquisas sobre a história de outras mulheres. A História das Mulheres sobre o crivo das respectivas historiadoras são representações de mulheres determinadas e dinâmicas que na condição de filhas, irmãs, esposas, mães, noras e sogras precisaram dar conta do trabalho, seja na pequena propriedade, na prestação de serviços e, também, como mão-de-obra na incipiente indústria de Caxias do Sul. As pesquisas das quatro historiadoras sobre as mulheres revelaram o protagonismo feminino na produção científica regional sobre a História das Mulheres, numa perspectiva de feminismos plurais. [resumo fornecido pelo autor]
Keywords: Professoras universitárias - Caxias do Sul (RS) - História; Mulheres - Caxias do Sul (RS) - História; Historiadoras; Ensino Superior - Rio Grande do Sul - História; Educação - Rio Grande do Sul - História; Women college teachers - Caxias do Sul (Brazil) - History; Women - Caxias do Sul (Brazil) - History; Women historians; Education, Higher - Rio Grande do Sul (Brazil) - History; Education - Rio Grande do Sul (Brazil) - History